PENGEMBANGAN DESA WISATA DAN PEMBANGUNAN PARIWISATA BERKELANJUTAN DESA WATUAJI - Tristan Alfian; Yayan Adi Saputro; Gun Sudiryanto (LPPM Universitas Abdurrab, 2021)
The tourism potential of Watuaji Village has unique rocks including watu gebyok, watu lawang, watu soko, watu stack and watu tatal. This is combined with a very stunning natural scenery because it is located on the northern slopes of Mount Muria, with the average occupation of the population being farming and gardening, Watuaji has views of stretches of rice fields as well as extensive avocado and coffee plantations. Natural conditions like this are very suitable for nature tourism and tourist villages. In Watuaji Village, POKDARWIS was formed in 2019 experiencing several problems with village funds that have not been disbursed for continuing development, road access to the location is still difficult, and there is no master plan. For this reason, our KKN team offers a solution in the form of making a master plan and garden layout in the Watu Stack area, so that it can be an alternative for short-term development, to continue long-term development in the Watu Gebyok area. The implementation method is carried out in 4 stages, namely analyzing with partners, collaborating with partners, working on plans and building friends. The target of achieving this KKN is to realize a tourist village in Watuaji village, so that it can increase the income of groups or surrounding communities in the context of economic and social recovery.